"Auschwitz erst möglich gemacht?" : Überlegungen zur jüngsten konservativen Geschichtsbewältigung - Donat, Helmut 1947- Hrsg; Wieland, Lothar 1952-; Beyrau, Dietrich 1942- (Donat, 1991)
Literaturverz. S. 152 - 214